PEMANFAATAN GEOPORTAL SUMBAR UNTUK MONITORING PETA TUTUPAN LAHAN PROVINSI SUMATERA BARAT MELALUI LAYANAN GEOSERVICES - firdaus ramadani; Arie Yulfa (JURNAL BUANA, 2026)
Utilization of the West Sumatra Geoportal studies the monitoring of spatial data access through Geoservices services. This study aims to monitor land cover maps available on the west Sumatra Geoportal through the Geoservices services available on the West Sumatra Geoportal. The method used in this research is quantitative descriptive with a Free and Open Source Software for Geospatial approach (FOSS4G) The results of this study indicate 1. There are benefits of Open Source applications in utilizing spatial data on the West Sumatra Geoportal web 2. There are differences in the results of spatial data on land cover maps 3. The importance of building scenarios to facilitate data collection on the West Sumatra Geoportal Web